2016
DOI: 10.1186/s40001-016-0209-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP1A1, GSTM1 and GSTT1 gene polymorphisms with risk of non-small cell lung cancer in Andhra Pradesh region of South India

Abstract: BackgroundLung cancer is one of the most preventable causes of death globally both in developed and developing countries. Although it is well established that smokers develop lung cancer, there are some smokers who are free from the disease risk. The predisposition to lung cancer is attributed to genetic polymorphisms in xenobiotic metabolizing genes. Reports on assessment of xenobiotic metabolizing genes like Cytochrome P 450 1A1 (CYP1A1), Glutathione -S -transferase M1 (GSTM1) and T1 (GSTT1) polymorphisms fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 54 publications
(65 reference statements)
1
21
0
Order By: Relevance
“…Thus, identification of smokers with high risks of developing lung cancer has substantial preventive implications, involving intensive screening and smoking cessation interventions or campaigns. Recent investigations show genetic association of several polymorphisms with lung cancer in a candidate gene based approach [Sobti et al, ; Parl, ; Sreeja et al, , Shah et al, ; Singh et al, ; Shukla et al, ; Singh and Behera, ; Phukan et al, ; Saikia et al, ; Shen et al, ; Sharma et al, ; Peddireddy et al, ]. A genome‐wide association study also revealed risk of lung cancer in never smokers, particularly women of East Asian origin and reported associations of several susceptibility loci, i.e., 10q25.2 (rs7086803, P = 3.54 × 10 ‐18 ), 6q22.2 (rs9387478, P = 4.14 × 10 ‐10 ) and 6p21.32 (rs2395185, P = 9.51 × 10 ‐9 ) [Lan et al, ] and with the malady.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, identification of smokers with high risks of developing lung cancer has substantial preventive implications, involving intensive screening and smoking cessation interventions or campaigns. Recent investigations show genetic association of several polymorphisms with lung cancer in a candidate gene based approach [Sobti et al, ; Parl, ; Sreeja et al, , Shah et al, ; Singh et al, ; Shukla et al, ; Singh and Behera, ; Phukan et al, ; Saikia et al, ; Shen et al, ; Sharma et al, ; Peddireddy et al, ]. A genome‐wide association study also revealed risk of lung cancer in never smokers, particularly women of East Asian origin and reported associations of several susceptibility loci, i.e., 10q25.2 (rs7086803, P = 3.54 × 10 ‐18 ), 6q22.2 (rs9387478, P = 4.14 × 10 ‐10 ) and 6p21.32 (rs2395185, P = 9.51 × 10 ‐9 ) [Lan et al, ] and with the malady.…”
Section: Discussionmentioning
confidence: 99%
“…a Forest plot for the odds ratios (ORs) of the SNP rs1048943 of CYP1A1 for the occurrence of lung cancer stratified by smoking status in sub-group analysis, b combined Forest plot, for the odds ratios (ORs) of the SNP rs1048943 of CYP1A1 for the occurrence of lung cancer stratified by smoking status in sub-group analysis between nonsmokers and smokers. [Sobti et al, 2003[Sobti et al, , 2004[Sobti et al, , 2008[Sobti et al, , 2009Parl, 2005;Sreeja et al, 2005, 2008a, Shah et al, 2008Singh et al, 2010Singh et al, , 2016Shukla et al, 2013;Singh and Behera, 2013;Phukan et al, 2014;Saikia et al, 2014;Shen et al, 2014;Sharma et al, 2015;Peddireddy et al, 2016]. A genome-wide association study also revealed risk of lung cancer in never smokers, particularly women of East Asian origin and reported associations of several susceptibility loci, i.e., 10q25.2 (rs7086803, P 5 3.54 3 10 -18 ), 6q22.2 (rs9387478, P 5 4.14 3 10 -10 ) and 6p21.32 (rs2395185, P 5 9.51 3 10 -9 ) [Lan et al, 2012] and with the malady.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental, life style and epigenetic factors are known to contribute to the risk of NSCLC. Among the epigenetic factors, genetic polymorphisms are predicted to be one of the major contributing factors for the occurrence of NSCLC . Genetic polymorphisms in genes belonging to different classes and their association with the risk of NSCLC were described .…”
Section: Introductionmentioning
confidence: 99%
“…In the first phase, the antioxidant defense is performed by the cytochrome P450 (CYP) enzymes. Furthermore, the defense in the second phase is done by the glutathione S-transferase (GSTs) enzymes and through conjugation of PAHs with glutathione GSH, which is the first stage of the mercapturic acid synthesis reaction that can prevent the damage in macromolecules (Mota et al, 2015;Peddireddy et al, 2016). GSTs (EC 2.5.1.18) have been identified as a superfamily of dopaminergic enzymes, which combine endogenous products derived from oxidative stress and electrophilic xenobiotics such as carcinogens, pesticides, drugs and bio-contaminating materials targeted (Hayes et al, 2005).…”
Section: Introductionmentioning
confidence: 99%